PERANCANGAN IDENTITAS VISUAL MUSEUM WAYANG POTEHI JOMBANG SEBAGAI UPAYA KONSERVASI BUDAYA - Sultan Arif Rahmadianto; Kevin Wibowo (Universitas Mercu Buana, 2020)
Technological developments such as television, internet, and smartphones that can be easily accessed are becoming more in demand by the younger generation than traditional performing arts. this is the cause of the decline of the existence of traditional art, especially wayang potehi. One of the museums that held a puppet art show potehi is Potehi Jombang Puppet Museum located in Raya Gudo area, Jombang, East Java. Potehi Puppet Museum is also affected by the many technological developments and other entertainment media. Therefore, it is necessary to visual identity of Potehi Jombang Puppet Museum as a step to introduce and preserve potehi puppet art because it is one of the cultures of acculturation in Indonesia. The design method used is a qualitative method. The result of this design is a visual identity in the form of Logo accompanied by the application in various media used as an effort to confectione Indonesian culture.